2021
DOI: 10.1007/s10071-021-01486-4
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion in the field: wild brown skuas find hidden food in the absence of visual information

Abstract: Inferential reasoning by exclusion allows responding adaptively to various environmental stimuli when confronted with inconsistent or partial information. In the experimental context, this mechanism allows selecting correctly between an empty option and a potentially rewarded one. Recently, the increasing reports of this capacity in phylogenetically distant species have led to the assumption that reasoning by exclusion is the result of convergent evolution. Within one largely unstudied avian order, i.e. the Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…Indeed, we are aware of only four studies that have experimentally tested waterbird cognition. These include two studies that experimentally tested the problem-solving skills of waterbirds (Olrog's gull: [ 23 ] brown skua: [ 24 ]), though neither employed the string-pull test paradigm. A third study showed a small number of horned puffins ( Fratercula corniculate , n = 5) to be unsuccessful at an object permanence test [ 60 ] which tests whether an individual comprehends that an object continues to exist when it is suddenly hidden from view [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, we are aware of only four studies that have experimentally tested waterbird cognition. These include two studies that experimentally tested the problem-solving skills of waterbirds (Olrog's gull: [ 23 ] brown skua: [ 24 ]), though neither employed the string-pull test paradigm. A third study showed a small number of horned puffins ( Fratercula corniculate , n = 5) to be unsuccessful at an object permanence test [ 60 ] which tests whether an individual comprehends that an object continues to exist when it is suddenly hidden from view [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Danel et al . [ 24 ] tested 26 free-living brown skuas ( Catharacta antarctica ssp. lonnberg ) with an exclusion test in which each subject was presented with two opaque cups—one empty and one containing food.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though olfaction previously has been dismissed as being unimportant for most bird species, it has turned out to play an important role in bird foraging behavior (Mäntylä et al, 2004;Hiltpold and Shriver, 2018;Potier, 2020;Danel et al, 2021). Some bird species can use their sense of smell to identify caterpillarinfested trees by detection of herbivore induced plant volatiles (HIPVs) (Mäntylä et al, 2004(Mäntylä et al, , 2020Amo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%